Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1002/jso.2930350411
|View full text |Cite
|
Sign up to set email alerts
|

Systemic rhabdomyosarcoma presenting as leukemia: Case report with ultrastructural study and reviews

Abstract: A 20-year-old white male was initially suspected clinically and pathologically of having an acute lymphoblastic leukemic process because of fatigue, severe anemia, thrombocytopenia, a leuko-erythroblastic peripheral blood picture, and a diffusely infiltrated bone marrow. Subsequent review of the bone marrow material indicated cytologic features consistent with either an embryonal, undifferentiated small cell mesenchymal malignancy or reticulo-endothelial malignancy. Ultimately, the electron microscopic (EM) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Multinucleated tumor cells and the tumor cells with hemophagocytic activity were also noted. [3][4][5][6][7][8][9] This cytologic spectrum has been documented with both alveolar and embryonal subtypes of RMS and therefore has no reference to the histologic variants. Cytomorphologically, our case bore a striking resemblance to those previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multinucleated tumor cells and the tumor cells with hemophagocytic activity were also noted. [3][4][5][6][7][8][9] This cytologic spectrum has been documented with both alveolar and embryonal subtypes of RMS and therefore has no reference to the histologic variants. Cytomorphologically, our case bore a striking resemblance to those previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Cytomorphologically, our case bore a striking resemblance to those previously reported. [3][4][5][6][7][8][9] Primary RMS, especially the alveolar subtype, is often recapitulated histologically by its metastases, including those seen in BM biopsy. 3, 10, 11 Reinecke, et al (1998) reported a case, in which the BM biopsy displayed an extensive tumorous infiltrate with the alveolar spaces lined by primitive round cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many of the reports, much emphasis has been placed on immunohistochemistry and/or electron microscopic examination as differential diagnostic approaches in cases of RMS with bone marrow involvement [4,[6][7][8][9]11,15,32,41]. As far as immunochemistry is concerned, the absence of the most common lymphocyte markers could be considered a possible consequence of dedifferentiation of the cells, therefore not excluding a highgrade lymphoma or acute leukemia [26].…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar rhabdomyosarcoma are small, blue, round-cell tumors requiring aggressive oncologic treatment. Depending on the location and stage, they can mimic other neoplasms, thus making the diagnostic process challenging [4,5,7].…”
Section: Short Reportmentioning
confidence: 99%